Hdac1 regulates differentiation of bipotent liver progenitor cells during regeneration via Sox9b and Cdk8 - Ko, Sungjin; Yuan, Xiaodong; Weng, Honglei (Gastroenterology, 2018)
Upon liver injury in which hepatocyte proliferation is compromised, liver progenitor cells (LPCs), derived from biliary epithelial cells (BECs), differentiate into hepatocytes. Little is known about the mechanisms of LPC differentiation. We used zebrafish and mouse models of liver injury to study the mechanisms.